Autocrine/paracrine involvement of insulin-like growth factor-I and its receptor in chronic lymphocytic leukaemia - Schillaci, Roxana (2005)
Chronic lymphocytic leukaemia (CLL) is characterized by the accumulation of long-lived B lymphocytes blocked in G(0/1) by impaired apoptosis. As insulin-like growth factor-I (IGF-I) is known for its antiapoptotic effects in different cell types, we investigated whether IGF-I and its receptor (IGF-IR) participate in autocrine/paracrine loops affecting the survival of CLL cells. IGF-IR protein and mRNA was present in CLL cells in 44% and 59% of patients respectively. IGF-IR expression in CLL patients was positively correlated with the expression of the antiapoptotic protein Bcl-2 and was involved in CLL cell survival in vitro. Serum IGF-I was elevated in CLL patients, but growth hormone (GH) was normal. CLL cells expressed IGF-I mRNA and secreted the growth factor in vitro. Therefore, local production of IGF-I can account for the increased levels of serum IGF-I, independently of GH, and may be related to autocrine/paracrine control of lymphocyte survival acting at IGF-IR. This is the first demonstration of IGF-IR expression in a subgroup of CLL patients and of its antiapoptotic effects in vitro, highlighting the importance of this growth factor receptor as a possible therapeutic target in CLL.